2008
DOI: 10.1007/s11771-008-0108-6
|View full text |Cite
|
Sign up to set email alerts
|

Hot deformation behaviors and flow stress model of GCr15 bearing steel

Abstract: The hot deformation behaviors of GCr15 bearing steel were investigated by isothermal compression tests, performed on a Gleeble-3800 thermal-mechanical simulator at temperatures between 950 ℃ and 1 150 ℃ and strain rates between 0.1 and 10 s −1 . The peak stress and peak strain as functions of processing parameters were obtained. The dependence of peak stress on strain rate and temperature obeys a hyperbolic sine equation with a Zener-Hollomon parameter. By regression analysis, in the temperature range of 950−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Based on experimental data and literature [30][31], it can be found that the critical strain ε c and ε 0.5 are function of initial grain size d 0 , deformation temperature T and strain rateε, and both of them can be described by equations which have the form similar to Eq. (7).…”
Section: Determination Of the Parameters For Drx Kineticsmentioning
confidence: 99%
“…Based on experimental data and literature [30][31], it can be found that the critical strain ε c and ε 0.5 are function of initial grain size d 0 , deformation temperature T and strain rateε, and both of them can be described by equations which have the form similar to Eq. (7).…”
Section: Determination Of the Parameters For Drx Kineticsmentioning
confidence: 99%
“…The hyperbolic-sine law is applicable for a wide range of stresses. It is now well accepted that the influence of strain rate and temperature on flow stress during hot deformation could be satisfactorily expressed with the equation proposed by Sellars and Tegart which takes hyperbolic form [11], as is shown in equation [3]:…”
Section: Phenomenological Equationsmentioning
confidence: 98%
“…By combining equation [3] and equation [4], we can relate the strain rate, temperature and the flow stress to Zener-Holloman parameter (Z):…”
Section: Phenomenological Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The understanding of metals and alloys behavior under hot deformation condition has a great importance to designers of metal forming processes because it can affect the required energy as well as the microstructure changes of deformed metal through work hardening, dynamic recovery (DRV) and DRX [1][2][3][4]. Constitutive equation, which relates to the stress, strain, strain rate and deformation temperature, is a powerful tool to describe material behavior during hot working.…”
Section: Introductionmentioning
confidence: 99%